2019
DOI: 10.1002/jcp.28090
|View full text |Cite
|
Sign up to set email alerts
|

LINC01857 as an oncogene regulates CREB1 activation by interacting with CREBBP in breast cancer

Abstract: Breast cancer is a one of the most malignant threats among women worldwide. However, the mechanism underlying breast cancer development remains unclear. Long noncoding RNAs (lncRNAs) have been reported to participate in breast cancer. Whether lncRNA LINC01857 is involved in breast cancer requires investigation. In this study, we found that LINC01857 was highly expressed in breast cancer tissues and cells (p < 0.05). High LINC01857 expression predicted poor prognosis in breast cancer patients. Functionally, LIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 26 publications
(40 reference statements)
0
20
0
Order By: Relevance
“… 25 Additionally, a recent study also showed that LINC01857 transcriptionally activates CREB1 expression through associating with CREBBP protein in BC and promotes tumor progression. 26 LCPAT1 has been reported to promote lung cancer cell proliferation, and it participates in DNA damage. 17 , 27 To our knowledge, whether LCPAT1 is involved in BC regulation remains totally unclear.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Additionally, a recent study also showed that LINC01857 transcriptionally activates CREB1 expression through associating with CREBBP protein in BC and promotes tumor progression. 26 LCPAT1 has been reported to promote lung cancer cell proliferation, and it participates in DNA damage. 17 , 27 To our knowledge, whether LCPAT1 is involved in BC regulation remains totally unclear.…”
Section: Discussionmentioning
confidence: 99%
“…16 In addition, increased expression of LINC01857, a CREB1 activator, was found to be linked to reduced survival time in patients with breast cancer. 17 As for in GC, an inhibitor of CREB1, miR-1297, was found to be poorly existed in GC patients and positively correlated with survival of patients. 18 Promotion of CREB1 in cancer has also been evidenced in several tumor cell types involving bladder cancer, 19 colorectal cancer 20 and glioma 21 cells.…”
Section: Discussionmentioning
confidence: 93%
“…We also found that LINC01857, LINC02446, and LINC02384, as protective factors of IL2R and IL7R, were potential oncogenic molecules, while miR‐203b‐3p and miR‐891a‐5p were suppressive of IL2RA and IL7R respectively. At present, there are still no reports about LINC01857 in malignant melanoma, and three reports indicating that LINC01857 was a potential oncogene in glioma, 40 breast cancer 41 and pancreatic cancer. 42 At the same time, there are no related literature on LINC02446 and LINC02384.…”
Section: Discussionmentioning
confidence: 99%